Transdermal uptake of substances banned in sports and its relevance for doping controls - Krombholz, S.; Korsmeier, L.; Thevis, M. (International Journal of Sports Medicine, 2025)
Transdermal drug delivery has emerged as an area of significant interest in both pharmaceutical sciences and antidoping research. This narrative review explores the implications of transdermal uptake of substances banned in sports, emphasizing its relevance for doping control analysis. The human skin`s complex role as both a barrier and a site of drug absorption is examined, alongside studies investigating the transdermal administration of substances on the World Anti-Doping Agency Prohibited List, including approved transdermal formulations and drug candidates. Recent cases demonstrate that (unintentional) dermal exposure of athletes to substances banned in professional sports, e.g., clostebol, can lead to an adverse analytical finding in doping controls. Consequently, studies investigating the detectability and metabolism of transdermally administered doping substances, which might even support identifying the route of exposure, are becoming increasingly important. This review emphasizes the relevance of addressing the skin as a pathway for both intentional doping and unintentional contamination, outlining critical implications for global antidoping efforts and future research priorities.